The evolution of Campylobacter : submitted in partial fulfilment of the requirements for the PhD in Statistical Genetics, mEpiLab, Infectious Disease Research Centre, Institute of Veterinary, Animal and Biomedical Sciences at Massey University, New Zealand - Yu, Shoukai (Massey University, 2012)
The genus Campylobacter is a major cause of human gastroenteritis worldwide, so understanding the evolution of Campylobacter has important implications. This multidisciplinary project uni es developments from statistics, genetics, bioinformatics and computer science and creates a good opportunity to investigate the evolution of Campylobacter by focusing on the factors which a ect genetic exchange. In order to understand how Campylobacter evolves, a mathematical method is put forward to estimate the relative rates of recombination and mutation in generating new alleles that lead to single locus variants (SLVs), and examine the e ect of selection, recombination and mutation. This analysis shows the importance of recombination in the evolution of Campylobacter and larger contribution made by recombination, compared to mutation, in the evolution of Campylobacter jejuni, and Campylobacter coli. In addition, this research demonstrates that purifying selection plays an important role in the evolution of Campylobacter. For comparison, this analysis also examined the role played by recombination in the evolution of other bacteria. This application highlighted the importance of recombination for creating diversity in closely related isolates. A range of phylogenetic and population genetic tools were applied to investigate the e ect of geographical isolation on the evolution of Campylobacter by comparing datasets from two geographically separated countries, New Zealand and the United Kingdom, this is the rst time this has been attempted. Analysing sequence data at di erent levels of resolution provided evidence that geographical isolation a ects the evolution of Campylobacter genotypes over short time-scales, but that this e ect diminishes over longer time-scales. Furthermore, this analysis estimates the time for divergence of NZ speci c lineages of Campylobacter strains. In New Zealand, Campylobacter jejuni strain type 474 (ST-474) is responsible for more than a quarter of human campylobacteriosis noti cations, but has been rarely found outside NZ. Knowing the clonal relationships of ST-474 strains is helpful for inferring the origin and the evolutionary mechanism of Campylobacter. This research accessed 59 isolates of Campylobacter. It applied a range of phylogenetic tools to targeted gene reference set to compare estimations of the clonal genealogy inferred for Campylobacter datasets. These ndings have implications for identifying the origin of Campylobacter, developing disease intervention strategies, predicting the emergence of pathogens, and reducing the occurrence of campylobacteriosis in the food supply chain.
Keywords: Campylobacter